Induction variable speed drive as the basis of efficient energy saving - Muravleva (Muravlyova) O. O. Olga Olegovna (2004, 2004)
Civilization tends to be in charge of power resources saving. The energetic theory, many applied sciences, including electrical engineering and electromechanics, study the ways and search for more economical solutions in electrical engineering, techniques and technologies. The purpose of the given paper is to determine the most effective ways of energy saving under the conditions of the country market economy transition from depression to development. It is necessary to use great potential of energy saving in Russia to solve the problems of energy saving. We suggest that induction variable speed drives should be used when solving the problem of energy saving.